TEACHING SPEAKING BY APPLYING TEAMS-GAMES-TOURNAMENTS TECHNIQUE - An Nisaa Rahmadani (LPPM IAI Almuslim Aceh, 2025)
The teams-games-tournaments technique used in this study is based on the students’ difficulty in the master of speaking skill. This technique aims to involve students’ speaking skill in their real life situation. The objective of this study is to investigate the students’ in the master after they practice speaking through teams-games-tournaments technique. In order to address issue, this study employed two groups as the sample classified into the experimental and control group. The experimental group was taught by using teams-games-tournaments technique, while the control group was taught by using traditional technique. In collecting the data, the test was used, and then the procedures in the collecting the data was experimental study. The research findings show that the mean score of the post-test of the experimental group, 79, is higher than that of the control group 53. Furthermore, the result of Z-score reveals that the score of experimental group is higher than that in the control group. The data indicates that the students taught by using teams-games-tournaments technique significantly achieved better score in speaking than those taught by using traditional technique.